Evaluation On Soil Organic Matter Status Of Merit Soils Under Various Cropping Systems - Shafinaz, Binti Shahabudin (Universiti Malaysia Sarawak (UNIMAS), 2007)
Soil organic matter greatly affects physical, chemical and biological properties of a particular soil. Increases of soil organic matter content are likely to increase soil nutrients, trace elements, aggregate stability and as well as likely to reduce soil crusting, bulk density and maintain soil pH, thereby, provide favourable medium for crop growth (Niang, 2004).